Corporate Tax Reduction Strategies: The Impacts of Institutional Ownership, Company Profitability, and Financial Leverage - Ni Putu Budiadnyani; Putu Pande R. Aprilyani Dewi; I Gede Joni Supriawan (Universitas Muhammadiyah Makassar, 2024)
Tax revenue is pivotal in funding crucial public services and infrastructure within a nation. Corporate tax avoidance strategies can have significant ramifications, undermining a country's capacity to adequately finance essential public systems such as education, public safety, transportation, and other vital community needs. The impact of corporate tax avoidance extends beyond individual firms, influencing the broader financial stability and economic development of the country. This study examines the influence of institutional ownership, profitability, and financial leverage on corporate tax avoidance practices. Drawing on agency theory and resource-based perspectives, the research investigates how these key firm-level factors shape tax minimization strategies. The findings indicate that institutional ownership and profitability do not have a significant effect on tax avoidance. However, increased financial leverage is associated with more aggressive corporate tax avoidance practices. The insights from this study contribute to the ongoing academic discourse on the ethical and economic implications of tax avoidance behaviors.